2016
DOI: 10.1080/2162402x.2015.1102827
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of circulating tumor cells and peripheral blood mononuclear cells from breast cancer patients

Abstract: Circulating tumor cells (CTCs) are cancer cells that are released from a tumor into the bloodstream. The presence of CTCs in peripheral blood has been associated with metastasis formation in patients with breast cancer. Therefore, the molecular characterization of CTCs may improve diagnostics and support treatment decisions.We performed gene expression profiling to evaluate the enriched CTCs and peripheral blood mononuclear cells (PBMCs) of breast cancer patients using an expression panel of 55 breast cancer-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 54 publications
3
32
0
1
Order By: Relevance
“…To further confirm the observation for ANO1 upregulation in ovarian tissues, we also isolated peripheral blood mononuclear cells (PBMCs) from patients with serous ovarian cancers and examined ANO1 mRNA expression in PBMCs in which some oncogene expressions have recently been shown to correlate with tumor grade and metastasis formation . As shown in Figure c , ANO1 mRNA expression in PBMCs was about 100‐fold higher in 9 out of 10 collected cases from serous ovarian cancer patients with an average value of 8 × 10 −3 relative to the expression of housekeeping gene ß‐actin, as compared to the value of 7.8 × 10 −5 for noncancer patients.…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…To further confirm the observation for ANO1 upregulation in ovarian tissues, we also isolated peripheral blood mononuclear cells (PBMCs) from patients with serous ovarian cancers and examined ANO1 mRNA expression in PBMCs in which some oncogene expressions have recently been shown to correlate with tumor grade and metastasis formation . As shown in Figure c , ANO1 mRNA expression in PBMCs was about 100‐fold higher in 9 out of 10 collected cases from serous ovarian cancer patients with an average value of 8 × 10 −3 relative to the expression of housekeeping gene ß‐actin, as compared to the value of 7.8 × 10 −5 for noncancer patients.…”
Section: Resultsmentioning
confidence: 77%
“…Therefore there is an urgent need to identify an early diagnostic biomarker for ovarian cancer. It has recently been shown that detection of gene expression profiling in PBMCs or circulating tumor cells may improve diagnostics and help make treatment decisions for breast cancer . Cytokines such as TNF network (TNF, IL6, CXCL12) are upregulated in serous ovarian cancer cell lines caused by oncogenic mutations and abnormal signaling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, whilst they supported the correlation between CTCs, metastatic process and patient's overall-survival, to date no consensus has been established regarding biological markers to be used to identify these cells [61][62][63] . Currently, putting together different studies, among all the analyzed genes related to cell survival (IGFR1, FOXO3), the EMT process (TWIST1, SNAIL, SLUG, VIM) or tumor progression and invasion (HER2, CXCR4, uPAR, VEGFA, VEGFR, Cathepsin D) only CK19, mucin 1 (MUC1) and EpCAM result as the most accepted genes [61,[64][65][66][67][68] . In addition, it has been demonstrated that metastasis exhibit, as primary tumors, an epithelial phenotype instead of a mesenchymal one, and that, using mice models, mammary tumors can promote an apparent EMT-independent lung metastatic process [69,70] .…”
Section: Ctcs and Their Plasticity In The Metastatic Processmentioning
confidence: 99%